Mathematical Simulation of Convective Heat Transfer in the Low-Temperature Storage of Liquefied Natural Gas; MATEC Web of Conferences; Vol. 37 : Smart Grids 2015 - Shestakov I. A. Igor (2015, 2015)
Title screen